Household Living Conditions - Piotr Białowolski; Janusz Czapiński; Izabela Grabowska; Irena E. Kotowska; Tomasz Panek; Paweł Strzelecki; Dorota Węziak-Białowolska (Contemporary Economics, 2011)
Household Living Conditions